Trauma and the (Im)Possibility of Representation: Patrick McGrath’s Trauma - Kerler, David (Cultura, Lenguaje y Representación, 2013)
Abstract: The present paper explores the notion of trauma as the epitome of the postmodern crises of representation and communication. Through the example of Patrick McGrath’s novel Trauma (2008), the trauma phenomenon will be scrutinized as thematic and aesthetic paradigm of contemporary literature. A close reading of McGrath’s novel shall elucidate trauma’s paradoxical structure of presence and absence, i.e. its call for articulation and simultaneous representational elusiveness. Special attention will be given to the narrative techniques and stylistic devices the text employs to give (an aesthetic) voice to the unspeakable. Abstracting from the results of these analyses, an aesthetics of the unrepresentable will be elaborated in the final section of the paper.